PENERAPAN METODE GLENN DOMAN UNTUK MENINGKATKAN KEMAMPUAN MEMBACA ANAK-ANAK TUNAGRAHITA - Amir, Yerni (JURNAL TAPIS, 2014)
The research is aimed at searching and providing an alternative method to increase the reading ability of the children with Mental Retardation. Mental retardation is the condition of mental development is limited and does not grow normally. Researches have prooved that the Glenn Domann Method can improve the Babyâs ability and injured children in reading. The reseacher conducted an action research by applying Glenn Doman method and then applied qualitative approach to analyze five students with special needs in the learning process of public elementary school for children with special needs. The research was investigating the implementation of the method in the teaching learning applied four times per week which spent thirty minutes per meeting. This research had been conducted within twenty four meetings in three months with three circles. The result of this reseach is that the implementation of Glenn Domann method did not significantly increase the reading ability of the mental retardation students. Students are more interested with the object drawn than the words provided. The no involvement of parents during research could be the factor why the influence is not significant. However,Â although the facts that the students have low intelligence and mental retardation became the crucial factors of the failure of the method, the positive movement and more concerns on the students with the same condition must always be committed.Keywords: Mental retardation, reading, glenn domann method